(untitled) (Journal of Medicine, 2014)
A cross sectional study was carried out in the department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka to explore the different clinical pattern of polyneuropathy. A total of 60 subjects were included in this study and mean age of the entire patient was 42.25 year and male and female ratio was 3:1. Out of all patients 26.7% were service holder, 20.0% were student, 20.0% were housewife, 11.7% were unemployed and 33.3% were engaged in some other professions. Maximum 41.7% patients were educated up to graduate and above level followed by 20.0% secondary, 18.3% primary, 16.7% higher secondary and 3.3% were illiterate. Out of all patients 31.7% were smoker, 48.3% were non smoker and 20.0% past smoker. About 35.0% patients had history of betel leaf; nut chewing and no patient had history of alcohol intake. Out of all patients of polyneuropathy 33.3% had diabetic neuropathy, 11.7% had Guillain-Barré syndrome (GBS), 10.0% had chronic inflammatory demyelinating polyneuropathy, similar number had unknown etiology, 6.7% had renal failure, 5.0% had leprosy, Vitamin B 12 deficiency and chronic liver disease(CLD) of each, 3.3% had history of INH drug intake and similar had systemic lupus erythematosus (SLE). Regarding clinical presentation, out of all respondents 83.3% had muscle weakness, similar number had problems with object handling, 66.3% had muscle cramp, 63.3% had impaired standing or gait, 55.0% had distal paresthesia, 41.7% had burning feet, 8.3% had restless legs and 5.0% had stiffness. In the light of this study we conclude that polyneuropathy has wide variety of clinical pattern. The study will enrich our current knowledge and will improve the quality of management of polyneuropathy among the Bangladeshi population. DOI: http://dx.doi.org/10.3329/jom.v15i1.19851 J Medicine 2014; 15: 3-8